(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article says that the early philosophers, continuing the worldview and humanistic principles of their predecessors and poets, showed that the world and its knowledge are relative. As the philosophers of the Kyrgyz people of the past, Kalygul Bai uulu, Arstanbek Buylash uulu and Moldo Kylych Shamyrkan uulu created an object of philosophical analysis in their work and raised the ideology of Kyrgyz public life. It tells about the role of the great scientist A. Altmyshbaev in Kyrgyz philosophy, who combined the works of the great philosophers of the world with the works of the great thinkers of Kyrgyzstan and made a great contribution to their scientific dissemination.